Effects of saline fluid on compressibility of clay minerals. Issue 2 (May 2014) - Tiwari, Binod; Ajmera, Beena
Abstract : Compressibility of the soil may change when it comes in contact with pore fluids of different chemistry. The possibility of having soil mass come in contact with saline pore fluid is always high for various reasons including the production of saline leachate in landfill sites, the movement of sea water into the groundwater when the latter is lower due to various reasons and frequent contact of soil along the coast with sea water. Forty-one soil samples were prepared in this study by mixing different proportions of various clay minerals such as montmorillonite, kaolinite and illite with each other and quartz. The liquid limits of these samples, measured with the distilled water, ranged from 12 to 486. These samples were mixed with 0·5 M sodium chloride (NaCl) solution to evaluate the effect of NaCl solution on the geotechnical properties of soil. A significant particle aggregation was observed in the NaCl-treated montmorillonite-dominated soils, which significantly reduced the clay fraction, Atterberg limits and compression indices. The effect of NaCl solution on changing geotechnical properties of illite and kaolinite was insignificant compared to the effect in montmorillonite. However, the NaCl-treated montmorillonite-dominated soils behaved similar to the illite- and kaolinite-dominated soils.